Moufang loops with nonnormal commutative centre. (10th May 2021) - GRISHKOV, ALEXANDER N.; ZAVARNITSINE, ANDREI V.
Abstract: We construct two infinite series of Moufang loops of exponent 3 whose commutative centre (i. e. the set of elements that commute with all elements of the loop) is not a normal subloop. In particular, we obtain examples of such loops of orders 3 8 and 3 11 one of which can be defined as the Moufang triplication of the free Burnside group B (3, 3).